Wireless digital data transmission from a 300 GHz CMOS transmitter. Issue 15 (1st July 2016) - Takano, K.; Katayama, K.; Amakawa, S.; Yoshida, T.; Fujishima, M.
Abstract : Wireless performance of a 300 GHz CMOS transmitter reported recently is presented. Wireless digital data transmission at 28 Gbit/s over 5 cm with 16‐QAM and 1 Gbit/s over 1 m with quaternary phase‐shift keying was achieved. A figure of merit (FoM) for transmit–receive systems that allows comparison of diverse configurations (with different modulation formats, antenna gains, distances, etc.) is introduced. The CMOS transmitter turns out to be comparable in performance to other 0.3 THz or higher systems involving compound‐semiconductor or photo‐mixing technologies. Analysis based on the FoM reveals how best use could be made of frequencies around 300 GHz with a CMOS technology.